Generating isolated terawatt-attosecond x-ray pulses via a chirped-laser-enhanced high-gain free-electron laser - Zhen Wang; Chao Feng; Zhentang Zhao (Physical Review Accelerators and Beams, 2017)
A feasible method is proposed to generate isolated attosecond terawatt x-ray radiation pulses in high-gain free-electron lasers. In the proposed scheme, a frequency chirped laser pulse is employed to generate a gradually varied spacing current enhancement of the electron beam, and a series of spatiotemporal shifters are applied between the undulator sections to amplify a chosen ultrashort radiation pulse from self-amplified spontaneous emission. Three-dimensional start-to-end simulations have been carried out, and the calculation results demonstrated that 0.15 nm x-ray pulses with a peak power over 1 TW and a duration of several tens of attoseconds could be achieved by using the proposed technique.